Penguatan Literasi Alam Kampung Ilmu Purwakarta - Amie Primarni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
The government's biggest homework now is how to improve remote areas, especially education issues. However, some groups have initiatives in building their own literacy centers in remote areas. It is a